Matching on Bipartite Graphs - Hans Gersbach; Hans Haller (Center for Economic Studies and ifo Institute (CESifo), 2015)
We study stable matchings on exogenously given or endogenously formed bipartite graphs that reflect constraints on matching. The effects of a change of the exogenously given graph (constraints) are investigated. Specifically, we examine to what extent individuals gain or lose from relaxing restrictions on matching. Sabotage of particular matches or location choice can render certain matches infeasible and, therefore, lead to endogenous constraints.
Keywords: C78; D02; D85; 330; matching theory; networks; graphs